Values of Progressive Education in the Novel entitled "Anak-Anak Cahaya" by Ramaditya Adikara - Devikasari, Fani; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: The purpose of this study is twofold: firstly, to analyze the educational values present in the novel "Anak-Anak Cahaya" (Children of Light) and secondly, to specifically examine the progressive educational values embedded within the narrative. Methodology: The research method used is a qualitative descriptive approach. The data collection technique of this research is note-taking technique. The data source for this research is the novel Anak-Anak Cahaya by Ramaditya Adikara. The research data is the intrinsic elements and educational values contained in the novel. The technique of testing the validity of the research data is carried out by testing the credibility. The data analysis technique of this research is descriptive qualitative. Results: The results of this study are the general educational values contained in the novel Anak-Anak Cahaya, namely religigious, honest, hard work, independent, friendly, social care, curiosity, love peace, and like to read. The novel Anak Anak Cahaya has educational values that are obtained based on the experiences of the characters. The values of progressive education in the novel Anak-Anak Cahaya are mutual helphave faith in Allah, mutual cooperation, and never give up. Applications/Originality/Value: Educational values contained in the novel Anak-Anak Cahaya, namely religious, honest, hard work, independent, friendly, social care, curiosity, love peace, and like to read. The novel Anak Anak Cahaya has educational values that are obtained based on the experiences of the characters. The values of progressive education in the novel Anak-Anak Cahaya are mutual help, have faith in Allah, mutual cooperation, and never give up.